Growth factor and galaxy bias from future redshift surveys: a study on parametrizations - Di Porto, Cinzia; Amendola, Luca; Branchini, Enzo (Arxiv, 2011)
Many experiments in the near future will test dark energy through its effects on the linear growth of matter perturbations. In this paper we discuss the constraints that future large-scale redshift surveys can put on three different parameterizations of the linear growth factor and how these constraints will help ruling out different classes of dark energy and modified gravity models. We show that a scale-independent bias can be estimated to a few percent per redshift slice by combining redshift distortions with power spectrum amplitude, without the need of an external estimation. We find that the growth rate can be constrained to within 2-4% for each $Δ z=0.2$ redshift slice, while the equation of state $w$ and the index $γ$ can be simultaneously estimated both to within 0.02. We also find that a constant dimensionless coupling between dark energy and dark matter can be constrained to be smaller than 0.14.